A systematic review of age-structured malaria transmission models (2019–2024) - Dinsa, Dechasa Wegi; Keno, Temesgen Duressa; Deressa, Chernet Tuge (Frontiers in Applied Mathematics and Statistics, 2024)
Malaria remains a serious and potentially fatal vector-borne disease, consistently ranking among the world’s deadliest infections. This study presents a systematic review of age-structured malaria transmission models. Articles were sourced from PubMed, Google Scholar, and the Research Gate Library, resulting in the identification and inclusion of eleven papers in the review. The findings highlight that children under the age of five are more susceptible to malaria than adults, due to their still-developing immune systems. The highest rates of morbidity and mortality are seen in youngsters, pregnant women, and people with impaired immune systems, making age structure a critical factor in the spread of malaria within populations. Personal protection and vector control are key strategies in reducing the transmission of malaria in communities. The study also suggests that the use of fractional operators in modeling could offer new insights into the dynamics of malaria transmission and potential control strategies.